Menduga Umur Simpan Kemplang yang Dimatangkan Menggunakan Microwave berdasarkan Persamaan Arrhenius - Parwiyanti, Parwiyanti; Yulistika, Efri; Rosidah, Umi; Lidiasari, Eka; Indriyani Syafutri, Merynda (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Parwiyanti, P., Yulistika, E., Rosidah, U., Lidiasari, E., & Syafutri, M. I. (2023). Estimation shelf life of microwavable fish crackers using the arrhenius reaction kinetics equation. In: Herlinda, S. et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 110-117). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Microwavable fish crackers had hygroscopic properties so it needs to be packaged properly. The objective of this research was to determine the shelf life of microwavable-packaged fish crackers. The fish crackers microwave was packed with three various method which are polypropylene (PP), PP + silica gel, and nylon + vacuum. Estimation of shelf life was done by calculating the parameters of degradation of microwavable fish crackers with the reaction kinetics equation and processed using the Arrhenius equation. The quality parameter was moisture content. Quality parameters are measured every 5 days during 30 days of storage at 30oC. The results showed that the kinetics of changes in the water content of microwavable fish crackers packed in three packaging combinations following reaction order one(1) and order two(2). The shelf life of microwavable fish crackers packaged in PP was 27 days, PP+silica gel packs was 29 days, and nylon+vacuum packs was 31 days.